Implementation of the SILATH Program to Strengthen Students' Language and Islamic Literacy at Junior High School - Ahmad Azhar; Rusydi Ananda; Muhammad Rifai (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the implementation of the SILATH Program (Sistem Literasi Langsung Setiap Hari, or Daily Direct Literacy System) as an effort to strengthen students' language literacy and Islamic literacy at SMP IT Ummi A'yuni Perbaungan. The study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students as research informants. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, which consists of data condensation, data display, and conclusion drawing and verification, while data credibility was ensured through source triangulation and methodological triangulation. The findings indicate that the SILATH Program is implemented systematically through planning, implementation, and continuous evaluation involving all school stakeholders. The program contributes to strengthening language literacy by improving students' reading, comprehension, communication, and reflection on reading content, while simultaneously enhancing Islamic literacy through habitual reading of Islamic literature, deeper understanding of Islamic values, and the development of students' religious character. Successful implementation is supported by the principal's commitment, active teacher involvement, and a conducive religious school environment. However, differences in students' reading interests, limited reading materials, and restricted implementation time remain challenges. Overall, the SILATH Program has proven to be an effective school strategy for fostering a sustainable literacy culture that integrates language literacy with Islamic literacy.